Implementasi Sistem Layanan Pengaduan Masyarakat Kecamatan Medan Amplas Berbasis Website - Yudha Sansena (Jurnal Ilmiah Teknologi Informasi Asia, 2021)
The more advanced the use of information technology, every government agency should strive to improve the quality of its services. One of them in the service of community complaints is a form of government participation to build and supervise the performance of government agencies in serving the community. In this study took a case study in Medan Amplas Subdistrict, Medan City where people still find it difficult to convey complaints in their neighborhood against the local government. So that people who do not understand spread their complaints in the wrong place. Therefore, there needs to be a website-based community complaint service system as an aspirational space that can be accessed easily. Website designing uses the Waterfallmethod, built with the sublime text 3 script language, PHP and Xampp 7.4.6 as its database, and testing systems using blackbox testing thus creating a website-based information system as a means to meet relevant public aspirations and available on the Internet.